Current expectations of the arterial switch operation in a small volume center: a 20-year, single-center experience. Issue 1 (December 2016) - Shim, Man-shik; Jun, Tae-Gook; Yang, Ji-Hyuk; Park, Pyo; Kang, I; Huh, June; Song, Jin
Abstract Background We reviewed our 20-year experience with arterial switch operation (ASO) for transposition of the great arteries (TGA) or double outlet right ventricle with subpulmonary ventricular septal defect (Taussig-Bing anomaly) to assess the early and long-term outcomes. Methods Between January 1995 and December 2014, 139 consecutive patients who underwent ASO for TGA or Taussig-Bing anomaly were included in this retrospective study. The median age at the operation was 9 (0–485) days, and 97 patients (70 %) underwent ASO less than 2 weeks. The median weight was 3.3 (2.1-10.3) kg. The patients were divided into three groups; simple TGA (n  = 78) included patients with TGA with intact ventricular septum, complex TGA (n  = 46) included those who had TGA with ventricular septal defect or other anomalies, and Taussig-Bing anomaly (n  = 15). Median follow-up duration was 72.5 (0.4-230) months. Results There were 3(2.2 %) in-hospital deaths. One patient (0.7 %) underwent early reoperation due to coronary insufficiency. Late deaths occurred in 3 (2.2 %) of 136 survivors. The Kaplan-Meier's survival rate was 97.6 ± 1.4 % at 15 years. Twenty-three patients (16.9 %) required 26 reintervention. The freedom from reintervention rates were 82.5 ± 3.7 % at 5 years and 75.8 ± 4.7 % at 10 years, respectively. Median interval between ASO and first reintervention was 22.8 (6.4-89.2) months. The multivariate analysis showed that diagnosis of Taussig-Bing anomaly (hazard ratio, 7.09;P  < 0.001) and side by side great artery relationship (hazard ratio, 7.98;P  = 0.001) were independent risk factors for reoperation. Five patients (3.9 %) had developed at least moderate neo-aortic regurgitation during the follow-up and one patient underwent reoperation mainly for neo-aortic regurgitation. By multivariate analysis, Taussig-Bing anomaly was the risk factor for at least moderate neo-aortic regurgitation (P  = 0.035). Conclusions ASO can be performed with a low risk of early mortality and satisfactory long-term outcomes even in a small volume center. Close long-term surveillance is mandatory to detect structural or hemodynamic changes.